2012
DOI: 10.4028/www.scientific.net/jnanor.21.71
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Titania Nanoparticles Synthesized by the Hydrothermal Method with Low Grade Mineral Precursors

Abstract: Abstract. The objective of this work is to utilize a low-grade synthetic rutile to produce high-grade titania nanoparticles. Due to the nature of the precursor, the hydrothermal method needs modification in order to accommodate the precursors and chemical reagents. The product will be characterized with the XRD (crystallite size and crystallinity), EDXRF (chemical composition), SEM (Morphology), N 2 adsorption-desorption (Surface Area) and UV-Vis-NIR. Results revealed a crystallite size of less than 20 nm, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…The result was similar to that reported in L. Jia and C. Li [6] [11]. Due to E. M. Mahdi, this is because a high concentrated sulphuric acid are containing more protons (H+) and sulphate ion, this is lead to the increasing of leaching rate [2].…”
Section: Titanium Dioxide Tio 2 Characterizationsupporting
confidence: 66%
“…The result was similar to that reported in L. Jia and C. Li [6] [11]. Due to E. M. Mahdi, this is because a high concentrated sulphuric acid are containing more protons (H+) and sulphate ion, this is lead to the increasing of leaching rate [2].…”
Section: Titanium Dioxide Tio 2 Characterizationsupporting
confidence: 66%
“…According to W. Zhang et al the ilmenite, leucoxene and rutile contains about 40-65%, more than 65% and 95% TiO 2 respectively [17]. Due to Mahdi, this is because high concentrated sulphuric acid contains more protons (H+) and sulphate ion, this leads to the increase of leaching rate [11]. The reaction rates at 2 M are higher than for 1 M samples and also show a bit difference for the 3 M samples.…”
Section: Resultsmentioning
confidence: 99%
“…There are so many extracting TiO 2 methods reported by previous researchers such as the template-assisted method [3], electrochemical anodic oxidation method [4], fiber laser ablation [5], modified molten salt process [6,7], hydrothermal treatment [8,9] and etc. In this study, we choose the caustic hydrothermal method as reported by many researchers [8][9][10][11][12]. Due to Ou, Paulus, and Mahdi et al, the caustic hydrothermal method can produce the TiO 2 in the powder form and this method can be simply modified in order to achieve a better characteristics of titanium powders [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium hydroxide was mixed with synthetic rutile at 550oC. The resulted TiO 2 NPs had smaller size (15.6 nm), higher absorbance of UV radiation and lower band gap (3.23) than commercial TiO 2 NPs[29].…”
mentioning
confidence: 99%